2017
DOI: 10.2147/ott.s110918
|View full text |Cite|
|
Sign up to set email alerts
|

RANKL/RANK pathway abrogates cetuximab sensitivity in gastric cancer cells via activation of EGFR and c-Src

Abstract: Overexpression of EGFR is commonly seen in gastric cancer (GC). However, patients with GC show resistance to anti-EGFR treatments. RAS mutations are rare in GC and cannot explain de novo resistance to EGFR treatments. Therefore, it is particularly important to explore the mechanisms of resistance to anti-EGFR treatments. The RANKL activates the EGFR pathway in osteoclasts, and the RANK is expressed in gastric carcinoma. Whether the RANKL/RANK pathway has an effect on the EGFR pathway in GC remains unknown. Exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…In our study, 56 gastric cancer specimens were collected. Our results suggested that patients with co-expression of CXCR4 and EGFR were more likely to have lymph node metastasis and poor prognosis, which is consistent with previous studies [ 4 , 13 ]. Furthermore, the impact of co-expression of CXCR4 and EGFR on prognosis in gastric cancer was investigated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, 56 gastric cancer specimens were collected. Our results suggested that patients with co-expression of CXCR4 and EGFR were more likely to have lymph node metastasis and poor prognosis, which is consistent with previous studies [ 4 , 13 ]. Furthermore, the impact of co-expression of CXCR4 and EGFR on prognosis in gastric cancer was investigated.…”
Section: Discussionsupporting
confidence: 93%
“…Immunohistochemical staining was performed as described previously [ 4 , 13 ]. Positivity (high expression) was defined as >10% of tumor cells showing staining in the sample.…”
Section: Methodsmentioning
confidence: 99%
“…RANKL stimulates RANK and has effects on the migration and invasion of cancer cells. Furthermore, RANKL/RANK function as predictors of tumorigenesis and prognosis in many solid tumors, including breast cancer and GC [18–20]. RANKL and its receptor, RANK, can be modulated by EGFR signaling [21].…”
Section: Discussionmentioning
confidence: 99%
“…CRC is the most common type of malignancy with the third highest incidence and mortality rates among all diagnosed cases of cancer worldwide ( 18 , 19 ). Cetuximab combined with chemotherapy has demonstrated therapeutic efficacy in patients with metastatic CRC with all RAS wild-type tumors ( 20 ). However, the efficacy of cetuximab is limited by the development of resistance mechanisms in cancer cells ( 21 ).…”
Section: Discussionmentioning
confidence: 99%